A design of fully soft robot actuated by gas–liquid phase change. (18th June 2019) - Nishikawa, Yuto; Matsumoto, Mitsuharu
Abstract : This study aims to investigate the application of temperature gradient between the ground and the air to the locomotion of soft robot. Soft robots attract attention due to its flexible adaptability and safety to the real environment in recent years. Although many soft robots are soft themselves, they require hard material as an external device such as air compressors and external power supplies for driving. To solve the problem, some authors reported an autonomous driving robot composed of a completely flexible material using gas generation by a chemical change of hydrogen peroxide solution. However, as the driving system utilizes a chemical reaction, its driving time is relatively short. On the contrary, the proposed robot moves without electricity and any external devices such as air compressors and an electrical power supplies. It can move just on the ground using the temperature gradient between the ground and the air. In experiments, we developed some prototypes and confirmed that continuous movement could be achieved with the proposed model. GRAPHICAL ABSTRACT: